Polyolefin-based resin foam particle, and polyolefin-based resin foam particle molding
Patent Information
- Application Number
- JP2023141120
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-13
AI Technical Summary
【0007】 本発明によれば、ポリオレフィン系樹脂発泡粒子の表面部分にケイ酸マグネシウムを存在させることにより、発泡倍率のバラツキが小さく抑えられた発泡粒子を得ることができる。また、成形体密度のバラツキが少ない発泡粒子成形体を得ることができる。
Smart Images

Figure 2025034628000001 
Figure 2025034628000002
Abstract
Description
[Technical field]
[0001] The present invention relates to expanded polyolefin resin beads and expanded polyolefin resin bead molded articles. [Background technology]
[0002] 2. Description of the Related Art Expanded polyolefin resin particles, such as expanded polypropylene resin particles, having through holes are known (Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2022-096231 Summary of the Invention [Problem to be solved by the invention]
[0004] , However, the expanded beads having through holes have a problem that the expansion ratio varies widely within and between production lots. Furthermore, when the expansion ratio of the expanded beads varies widely, the molding density of the resulting expanded bead molding also varies widely, and it may not be easy to produce expanded bead moldings of consistent quality.
[0005] In view of the above-mentioned problems, the present invention aims to provide expanded polyolefin resin beads having through holes, which have a small variation in expansion ratio, and to provide an expanded bead molding having a small variation in molding density. [Means for solving the problem]
[0006] According to the present invention, there are provided the following expanded polyolefin resin beads and expanded polyolefin resin bead molded articles. [1] A polyolefin-based resin expanded particle having through holes, characterized in that magnesium silicate is present on the surface portion of the expanded particle, and the proportion of magnesium silicate on the surface portion of the expanded particle is 0.1 mass% or more. [2] The expanded polyolefin resin particles according to [1], wherein the average pore diameter d of the through holes of the expanded polyolefin resin particles is 0.1 mm or more and 5 mm or less. [3] The polyolefin resin expanded particles according to [2], wherein the average pore diameter d of the through holes of the polyolefin resin expanded particles is 0.1 mm or more and less than 1 mm, and the ratio d / D of the average pore diameter d to the average outer diameter D of the polyolefin resin expanded particles is 0.4 or less. [4] The expanded polyolefin resin particles according to [3], wherein the average outer diameter D of the expanded polyolefin resin particles is 2 mm or more and 5 mm or less, and the average wall thickness t of the expanded polyolefin resin particles is 1.2 mm or more and 2 mm or less. [5] The expanded polyolefin resin particles according to any one of [1] to [4], wherein the expanded polyolefin resin particles have a polyolefin resin foamed layer and a polyolefin resin coating layer, and the coating layer covers all or a part of the expanded layer. [6] A polyolefin resin foamed bead molding obtained by molding the foamed beads according to any one of [1] to [5] in a mold. Effect of the Invention
[0007] According to the present invention, by allowing magnesium silicate to exist on the surface portion of the expanded polyolefin resin beads, it is possible to obtain expanded beads with small variations in expansion ratio, and to obtain expanded bead moldings with small variations in molding density. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The expanded polyolefin resin beads and the expanded polyolefin resin bead molded article of the present invention will be described in detail below in this order.
[0009] The subject of the present invention is polyolefin-based resin expanded particles (hereinafter simply referred to as expanded particles) having through holes, and the expanded particles include expanded particles consisting of a single layer of polyolefin-based resin foamed layer and multi-layer expanded particles having a polyolefin-based resin foamed layer and a polyolefin-based resin coating layer.
[0010] Next, the resin constituting the expanded beads of the present invention will be described. When the expanded beads are single-layered expanded beads, the resin constituting the expanded beads is a polyolefin resin, and when the expanded beads are multi-layered expanded beads, the resin constituting the foam layer is a polyolefin resin. In this specification, the polyolefin resin refers to a homopolymer of an olefin monomer such as ethylene, propylene, butene, or pentene, or a copolymer containing 50 mol % or more of a component derived from an olefin monomer.
[0011] Examples of the polyolefin resin include polyethylene resin, ethylene ionomer, polypropylene resin, polybutene, polypentene, and copolymers of olefin monomers and monomers copolymerizable with olefin monomers such as styrene monomers. Among these, polypropylene resin and polyethylene resin are preferably used, and polypropylene resin is particularly preferred. In addition, polyolefin resins derived from post-consumer waste materials (PCR) and automobile scrap (ASR) can also be used as the polyolefin resin.
[0012] Examples of the polyethylene-based resin include ethylene homopolymers such as high-density polyethylene, medium-density polyethylene, branched low-density polyethylene, linear low-density polyethylene, and linear very low-density polyethylene; and ethylene copolymers containing 50 mol% or more of a component derived from an ethylene-based monomer, such as ethylene-propylene random copolymers, ethylene-propylene block copolymers, ethylene-butene block copolymers, ethylene-butene random copolymers, ethylene-vinyl acetate copolymers, and ethylene-methyl methacrylate copolymers.
[0013] Examples of the polypropylene-based resin include propylene homopolymers such as isotactic polypropylene, syndiotactic polypropylene, and atactic polypropylene; propylene-based copolymers containing 60 mol% or more of a component derived from a propylene-based monomer, such as a propylene-ethylene random copolymer, a propylene-ethylene block copolymer, a propylene-butene random copolymer, a propylene-butene block copolymer, a propylene-ethylene-butene terpolymer, a propylene-acrylic acid copolymer, and a propylene-maleic anhydride copolymer.
[0014] When the expanded beads are made of a polypropylene resin, the melting point Tmc is preferably 120°C or more and 160°C or less. In this case, an expanded bead molding having an excellent balance between the moldability in the mold of the expanded beads and the mechanical properties of the obtained molding can be stably obtained. From the viewpoint of improving the mechanical properties of the obtained molding, the melting point Tmc of the polypropylene resin constituting the expanded beads is preferably 130°C or more, more preferably 135°C or more. In addition, from the viewpoint of improving the moldability in the mold under low molding pressure conditions, the melting point Tmc of the polypropylene resin constituting the expanded beads is preferably 155°C or less, more preferably 153°C or less.
[0015] In this specification, the melting point of the polypropylene resin is determined based on JIS K7121:1987. Specifically, the conditioning is performed by "(2) Measuring the melting temperature after a certain heat treatment", and the conditioned test piece is heated from 30°C to 200°C at a heating rate of 10°C / min to obtain a DSC curve, and the apex temperature of the melting peak is taken as the melting point. When multiple melting peaks appear on the DSC curve, the apex temperature of the melting peak with the largest area is taken as the melting point.
[0016] In addition, the polyolefin resin constituting the expanded beads of the present invention may contain other resins than the polyolefin resin, such as other resins and elastomers, within a range that does not impair the object and effect of the present invention. Examples of resins other than the polyolefin resin include thermoplastic resins such as polystyrene resins, polyamide resins, and polyester resins. Examples of elastomers other than the polyolefin resin include olefin thermoplastic elastomers and styrene thermoplastic elastomers. The other resins and elastomers are preferably contained in the polyolefin resin in an amount of 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less.
[0017] Next, the through holes formed in the expanded beads of the present invention will be described. The expanded beads of the present invention have through holes. When the expanded beads have through holes, the expanded beads can be given physical properties derived from the through holes, or can have air permeability derived from the through holes, and can have properties different from those of expanded beads without through holes. Examples of the cross-sectional shape of the expanded beads having the through holes include (a) a hollow circular shape (doughnut shape), (b) a hollow triangular shape, (c) a hollow hexagonal shape, (d) a shape with a partition in a hollow circle, (e) a shape of two hollow circles arranged side by side, (f) a shape of three hollow circles arranged side by side in contact with each other, (g) a hollow circular shape with a break in part, and (h) a hollow rectangular shape with a break in part. Examples of the through holes include a cylindrical shape with a constant hole diameter from one opening end to the other opening end, and a tapered hole.
[0018] The average pore diameter d of the through holes is preferably 0.1 mm or more and 5 mm or less. From the viewpoint of further improving the appearance of the molded article, further improving the compressive strength, and further improving the secondary expandability of the expanded beads, the average pore diameter d of the expanded beads is preferably less than 1 mm, more preferably 0.9 mm or less, even more preferably 0.85 mm or less, even more preferably 0.8 mm or less, and particularly preferably 0.7 mm or less. From the viewpoint of ease of production, the lower limit of the average pore diameter d of the expanded beads is approximately 0.1 mm, preferably 0.3 mm, more preferably 0.4 mm, and even more preferably 0.5 mm.
[0019] The average diameter d of the through holes is determined as follows: 50 or more expanded beads randomly selected from a group of expanded beads are cut perpendicularly to the penetration direction of the through holes at the position where the area of the cut surface is maximum. A photograph of the cut surface of each expanded bead is taken, the cross-sectional area of the through hole portion (specifically, the opening area) is determined, and the diameter of a virtual perfect circle having the same area as that area is calculated. The arithmetic mean of these values is taken as the average diameter d of the through holes.
[0020] The average outer diameter D of the expanded beads is preferably 2 mm or more, more preferably 2.5 mm or more, and even more preferably 3 mm or more. On the other hand, the average outer diameter D is preferably 6 mm or less, more preferably 5 mm or less, and even more preferably 4 mm or less. When the average outer diameter D is within the above range, the foamed beads are more easily filled into the mold during in-mold molding, and the rigidity of the molded product is increased.
[0021] The ratio d / D of the average pore diameter d to the average outer diameter D of the expanded beads is preferably 0.8 or less. In addition, from the viewpoint of improving the appearance of the molded body, preventing a decrease in strength during compression, and preventing a decrease in secondary expandability of the expanded beads during molding in a mold, the ratio d / D of the average pore diameter d to the average outer diameter D of the expanded beads is preferably 0.4 or less. From the viewpoint of improving the appearance of the molded body, improving the compression strength, and improving the secondary expandability, the ratio d / D is more preferably 0.35 or less, even more preferably 0.3 or less, even more preferably 0.25 or less, and particularly preferably less than 0.2. On the other hand, if the ratio d / D is too small, production may be difficult, so it is preferably 0.1 or more.
[0022] The average outer diameter D of the expanded beads is determined as follows: 50 or more expanded beads randomly selected from a group of expanded beads are cut perpendicularly to the penetration direction of the through holes at the position where the area of the cut surface is maximum. A photograph is taken of the cut surface of each expanded bead to determine the cross-sectional area of the expanded bead (specifically, the cross-sectional area including the opening of the through hole), and the diameter of a virtual perfect circle having the same area as that area is calculated. The arithmetic mean of these values is taken as the average outer diameter D of the expanded beads.
[0023] The average value of the wall thickness t of the expanded beads is preferably 0.5 mm or more and 2 mm or less. From the viewpoint of the expanded beads having a sufficiently thick wall thickness and further improving the secondary foaming property during molding in a mold, the average value of the wall thickness t of the expanded beads is preferably 1.2 mm or more and 2 mm or less. From the viewpoint of the expanded beads being more resistant to crushing by external forces and further improving the compressive stress of the molded body, the average wall thickness t of the expanded beads is more preferably 1.3 mm or more, and further preferably 1.4 mm or more.
[0024] The wall thickness t of an expanded bead is the distance from the surface portion (ie, the outer surface portion) of the expanded bead to the outer edge of the through-hole (ie, the inner surface portion of the expanded bead), and is calculated by the following formula (1). t = (Dd) / 2 (1) d: Average hole diameter of through hole (mm) D: Average outer diameter of foam particles (mm)
[0025] The ratio t / D of the average wall thickness t to the average outer diameter D of the expanded beads is preferably 0.1 or more and 0.5 or less. From the viewpoint of good filling properties of the expanded beads and further improving secondary expandability during in-mold molding of the expanded beads, the ratio t / D of the average wall thickness t to the average outer diameter D of the expanded beads is preferably 0.35 or more and 0.5 or less. If the ratio t / D is within the above range, a molded product having excellent rigidity can be produced at a lower molding heating temperature.
[0026] When through holes are formed in the expanded beads, the expansion ratio of each expanded bead tends to vary widely. The reason for this is believed to be as follows. Water used during the production of the expanded beads is likely to remain in the through holes. Furthermore, the amount of water remaining in the through holes tends to increase and vary. This is believed to result in unstable expansion conditions, leading to large variations in the expansion ratio of each expanded bead. The present inventors have found that by having a specific amount of magnesium silicate present on the surface portion of the expanded beads, water is effectively prevented from remaining in the through holes, and the variation in the expansion ratio of the obtained expanded beads can be reduced.
[0027] In the expanded beads of the present invention, magnesium silicate is present on the surface thereof, and since the surface free energy of magnesium silicate is extremely low, the surface free energy of the expanded beads surface is kept low, and it is considered that the wettability of the expanded beads is maintained low, and water is less likely to remain in the expanded beads, particularly in the through-holes.
[0028] In this specification, the presence of magnesium silicate on the surface portion of an expanded bead means an embodiment in which magnesium silicate is attached to the surface of an expanded bead, an embodiment in which the resin on the surface portion of an expanded bead contains magnesium silicate, and an embodiment in which magnesium silicate is attached and also the resin on the surface portion of an expanded bead contains magnesium silicate.
[0029] Specifically, it is preferred that magnesium silicate be present on the surface of the single-layer or multi-layer expanded beads, and that magnesium silicate be adhered to the surface of the expanded beads. As a method for adhering magnesium silicate to the surface of expanded beads, a method is preferably adopted in which magnesium silicate is used as a dispersant in the dispersion medium release foaming method described below, in which magnesium silicate functions as a dispersant and magnesium silicate is adhered to the surface portion of the expanded beads. However, the present invention is not limited to the dispersion medium release foaming method, and other methods may be used as long as magnesium silicate can be present on the surface of the expanded beads. For example, there are a method of applying a dispersion liquid in which magnesium silicate is dispersed to the expanded beads to attach magnesium silicate to the surface of the expanded beads, a method of adding magnesium silicate to a resin constituting the expanded beads to be contained in the expanded beads, and a method of containing magnesium silicate in the coating layer of a multi-layer expanded bead.
[0030] The surface portion of the expanded beads refers to the range from the outer surface portion of the expanded beads to 20 μm inward, and when magnesium silicate is attached to the surface of the expanded beads, the magnesium silicate attached to the surface of the expanded beads is also included in the magnesium silicate present in the surface portion. It is considered that the presence of magnesium silicate in the above range allows the expanded beads to exhibit hydrophobicity, and allows the production of expanded beads with small variation in expansion ratio.
[0031] In the present invention, the abundance ratio of magnesium silicate in the surface portion of the expanded beads is a value calculated as the sum of the adhesion ratio and content ratio of magnesium silicate to the expanded beads, and is 0.1% by mass or more relative to 100% by mass of the expanded bead body. If the abundance ratio is too low, the effect of the present invention may not be obtained. From this viewpoint, the abundance ratio of magnesium silicate is preferably 0.15% by mass or more, more preferably 0.2% by mass or more, and even more preferably 0.3% by mass or more. The upper limit of the abundance ratio is approximately 3% by mass or less, and from the viewpoint of preventing a decrease in the fusibility of the expanded beads, it is preferably 2% by mass or less, more preferably 1% by mass or less, and most preferably 0.8% by mass or less.
[0032] The proportion of magnesium silicate present on the surface of the expanded beads in the present invention can be measured as follows. For example, in the case where magnesium silicate is attached to the expanded beads, the ash content (A1: wt%) of the expanded beads and the ash content (A2: wt%) of the resin particles before being subjected to the expanded bead manufacturing process are measured, and the content ratio of magnesium silicate present on the surface of the expanded beads can be determined by subtracting the ash content (A2: wt%) of the resin particles from the ash content (A1: wt%) of the expanded beads. Also, the ash content (A1: wt%) of the expanded beads and the ash content (A3: wt%) of the expanded beads from which the attached content has been physically or chemically removed are measured, and the content ratio of magnesium silicate present on the surface of the expanded beads can be determined by subtracting the ash content (A3: wt%) of the expanded beads from which the attached content has been removed from the ash content (A1: wt%) of the expanded beads. The ash content includes inorganic components other than magnesium silicate, but the amount of magnesium silicate adhering can be measured by determining the proportion of magnesium silicate in the ash separately using X-ray fluorescence analysis or the like.
[0033] When magnesium silicate is contained in the surface portion of the expanded beads, the content can be measured, for example, by a method in which a portion up to 20 μm from the surface of the expanded beads is scraped off and the ash content is measured, or by a method in which an ATR spectrum of the surface portion of the expanded beads is measured and a calibration curve for magnesium silicate is separately prepared, and the content is measured by comparing the spectrum.
[0034] In the present invention, the method of causing magnesium silicate to be present on the surface portion of expanded beads is preferably a method in which magnesium silicate is used as a dispersant in a dispersion medium release foaming method described below, in which magnesium silicate functions as a dispersant and, in addition, magnesium silicate is adhered to the surface portion of resin particles described below, and the resin particles are then foamed.
[0035] Next, the moisture content of the expanded beads will be described. The water content of the expanded beads of the present invention is preferably 0.1% by mass or more and 2.5% by mass or less. If the water content is within this range, the variation in the expansion ratio of the resulting expanded beads can be reduced. From this viewpoint, the lower limit of the water content is more preferably 0.2% by mass, and even more preferably 0.4% by mass. Meanwhile, the upper limit of the water content is more preferably 2.3% by mass, and even more preferably 2.1% by mass.
[0036] In addition, when the moisture content of the expanded beads is high, the moisture content of each expanded bead tends to vary widely. In such a case, the weight of each expanded bead varies, making it difficult to stably fill a constant amount of expanded beads into a mold, and the molding density of the expanded bead molding after molding in the mold also varies widely. The above problem can be solved by reducing the moisture content of the expanded beads, but adding a drying process leads to a deterioration in production efficiency.
[0037] The moisture content is measured as follows: In the present invention, the moisture content of the expanded particles can be measured using a halogen moisture meter, and a specific example of the measuring device is a halogen moisture meter (HX204) manufactured by METTLER TOLEDO, which measures the moisture content based on halogen lamp heating. Specifically, the moisture content of the expanded beads can be measured by the following method. First, the expanded beads obtained by the expansion process and cured are weighed to obtain a measurement sample. Next, the measurement sample is heated to a temperature of 100°C using a halogen moisture meter and maintained at 100°C for 60 seconds until no weight change occurs, and then further heated to 160°C and maintained at 160°C for 90 seconds until no weight change occurs, thereby vaporizing the moisture inside the measurement sample. The weight loss due to heating at this time is divided by the weight of the expanded beads before heating and converted into a percentage to calculate the moisture content (%).
[0038] Next, the inclusion of carbons in the foamed beads will be described. The expanded beads of the present invention preferably contain carbons from the viewpoint of improving the appearance by being colored black.
[0039] The content of carbons in the expanded beads is preferably 0.1% by mass or more and 5% by mass or less, more preferably 0.5% by mass or more and 4% by mass or less, and even more preferably 1% by mass or more and 3% by mass or less, when the expanded beads are single-layer expanded beads. On the other hand, when the expanded beads are multi-layer expanded beads, it is preferable that at least the coating layer contains carbons. The content of carbons in the coating layer is preferably 0.1% by mass or more and 5% by mass or less, more preferably 0.5% by mass or more and 4% by mass or less, and even more preferably 1% by mass or more and 3% by mass or less. Furthermore, the foam layer can also contain carbons. In this case, the content of carbons in the foam layer is preferably 0.1% by mass or more and 5% by mass or less, more preferably 0.5% by mass or more and 4% by mass or less, and even more preferably 1% by mass or more and 3% by mass or less.
[0040] The carbon content in the expanded beads and the molded bodies thereof can be quantified by the TG-DTA method. Specifically, a sample cut out from the expanded beads or the molded body in the mold is used as a measurement sample, and the weighed sample is heated from 40°C to 600°C in a nitrogen atmosphere. Next, the heating temperature is lowered to 400°C, the atmospheric gas is changed from nitrogen to air, and the sample is heated to 800°C. The weight loss amount when heated to 600°C in a nitrogen atmosphere is the organic matter amount, and the weight loss amount when heated to 800°C under an air atmosphere is the carbon content amount. When measuring the content of the coating layer, the target part can be scraped off as a sample and measured in the same manner.
[0041] The carbons include at least one type of carbon powder selected from carbon black, carbon nanotubes, graphite, graphene, carbon nanofibers, carbon microfibers, carbon microcoils, and carbon nanocoils, and examples of the carbons that can be used include channel black, roller black, furnace black, thermal black, acetylene black, SWCNT, MWCNT, branched MWCNT, etc. Among these, furnace black is preferable as the carbons used in the expanded beads because it has an excellent balance between dispersibility in polypropylene-based resins and material costs.
[0042] When carbons are contained in the expanded beads of the present invention, the mass ratio of the amount of magnesium silicate present on the surface portion of the expanded beads to the amount of carbons contained in the expanded beads (CB / magnesium silicate amount) is preferably 2.5 or more and 100 or less, and more preferably 3 or more and 50 or less.
[0043] (Other additives) The expanded beads of the present invention may contain additives. Specifically, additives such as flame retardants, flame retardant assistants, cell regulators, antioxidants, weathering agents, crystal nucleating agents, etc. may be contained in the entire single-layer expanded beads, the entire multi-layer expanded beads, or only in the coating layer of the multi-layer expanded beads.
[0044] Next, the bulk density and crystal structure of the expanded beads of the present invention will be described. (Expanded particle bulk density) The bulk density of the foam particles is 10 kg / m 3 More than 500kg / m 3 If the bulk density is within this range, the resulting molded article will have a good balance between light weight and rigidity. From this viewpoint, the bulk density of the expanded beads is preferably 15 kg / m or less. 3 More than 100kg / m 3 More preferably, it is 18 kg / m or less. 3 More than 50kg / m 3 It is even more preferable that:
[0045] The bulk density of expanded beads is measured by the following method. First, the expanded beads to be measured are left to stand for at least 24 hours in an environment with a temperature of 23°C, relative humidity of 50%, and 1 atm. After that, a mass W (unit: g) of expanded beads is filled into a measuring cylinder, and the bottom of the measuring cylinder is lightly tapped on the floor several times to stabilize the filling height of the expanded beads in the measuring cylinder. The bulk volume V (unit: L) of the expanded beads indicated by the graduations on the measuring cylinder is read, and the mass W of the expanded beads is divided by the bulk volume V of the expanded beads (i.e., W / V). The value obtained in this way is expressed in kg / m 3 The bulk density of the expanded beads (unit: kg / m) was calculated by converting the unit to the mass ratio, repeating the same measurement for different samples, and calculating the average. 3 ) can be obtained.
[0046] Next, the crystal structure of the expanded beads of the present invention, as analyzed by differential scanning calorimetry (DSC), will be described. (High temperature peak) The expanded beads preferably have a crystal structure in which a melting peak specific to the polypropylene resin (i.e., a peak specific to the resin) and one or more melting peaks (i.e., high-temperature peaks) appear on the higher temperature side of the DSC curve obtained when the expanded beads are heated from 23° C. to 200° C. at a heating rate of 10° C. / min. The DSC curve is obtained by differential scanning calorimetry (DSC) in accordance with JIS K7121:1987 using 1 to 4 mg of the expanded beads as a test sample. The resin-specific peak is an endothermic peak due to the melting of crystals specific to the polypropylene resin constituting the expanded beads, and is considered to be due to the endothermic heat generated when the crystals of the polypropylene resin usually melt. On the other hand, the endothermic peak on the high temperature side of the resin-specific peak (i.e., the high-temperature peak) is an endothermic peak that appears on the higher temperature side than the resin-specific peak in the DSC curve. When this high-temperature peak appears, it is presumed that a secondary crystal component with a high melting point exists in the resin. In addition, in the DSC curve obtained by heating from 23°C to 200°C at a heating rate of 10°C / min (i.e., the first heating) as described above, cooling from 200°C to 23°C at a cooling rate of 10°C / min, and then heating from 23°C to 200°C at a heating rate of 10°C / min again (i.e., the second heating), only the endothermic peak due to the melting of crystals specific to the polypropylene resin constituting the expanded beads is observed, so that the resin-specific peak and the high-temperature peak can be distinguished. The temperature at the apex of this resin-specific peak may differ slightly between the first and second heatings, but the difference is usually within about 5°C.
[0047] The heat of fusion of the high-temperature peak of the expanded beads is preferably 5 J / g or more and 40 J / g or less, more preferably 7 J / g or more and 30 J / g or less, and even more preferably 10 J / g or more and 20 J / g or less, from the viewpoint of further improving the moldability of the expanded beads and obtaining molded bodies with superior rigidity. The total heat of fusion of the expanded beads is preferably 25 J / g or more and 150 J / g or less, more preferably 35 J / g or more and 100 J / g or less, and even more preferably 50 J / g or more and 90 J / g or less.
[0048] (Method of measuring high temperature peaks) The heat of fusion of each peak of the DSC curve of the expanded beads is a value obtained as follows. First, about 1 to 4 mg of expanded beads are collected from the expanded beads after conditioning. The expanded beads are used as test pieces, and a DSC curve is obtained when the test pieces are heated from 23°C to 200°C at a heating rate of 10°C / min using a differential scanning calorimeter. Note that a plurality of expanded beads may be used as the test pieces. The DSC curve shows a resin-specific peak ΔH1 and a high-temperature peak ΔH2 having a peak at a higher temperature side than the peak of the resin-specific peak ΔH1. Next, a line L1 is obtained by connecting point α at 80°C on the DSC curve with point β at the melting end temperature T of the expanded beads. Next, a line L2 parallel to the vertical axis of the graph is drawn from point γ on the DSC curve, which corresponds to the valley between the resin intrinsic peak ΔH1 and the high-temperature peak ΔH2, and the point where line L1 and line L2 intersect is designated as δ. Point γ can also be regarded as a maximum point existing between the resin intrinsic peak ΔH1 and the high-temperature peak ΔH2. The area of the resin intrinsic peak ΔH1 is the area surrounded by the curve of the resin intrinsic peak ΔH1 portion of the DSC curve, the line segment α-δ, and the line segment γ-δ, and this is the heat of fusion of the resin intrinsic peak. The area of the high-temperature peak ΔH2 is the area surrounded by the curve of the high-temperature peak ΔH2 portion of the DSC curve, the line segment δ-β, and the line segment γ-δ, and this is the heat of fusion of the high-temperature peak (i.e., the high-temperature peak heat quantity). The area of the total melting peak is the area surrounded by the curve of the resin-specific peak ΔH1 part of the DSC curve, the curve of the high-temperature peak ΔH2 part, and the line segment α-β (i.e., straight line L1), and this is the heat of fusion of the total melting peak (total heat of fusion).
[0049] Next, in the present invention, multi-layer expanded beads can also be used as the expanded beads. The multi-layered expanded particles have a polyolefin resin foam layer and a polyolefin resin coating layer, and the coating layer covers all or a part of the foam layer. That is, the multi-layered expanded particles are composed of the foam layer made of the polyolefin resin and the coating layer that covers all or a part of the foam layer, and as a whole, a so-called sheath-core structure is formed. When a sheath-core structure is formed, even if the amount of magnesium silicate attached to the surface of the expanded beads increases, the resin of the coating layer has excellent fusion properties, so that a decrease in the fusion properties between the expanded beads can be prevented.
[0050] The coating layer is composed of a polyolefin resin in a foamed or non-foamed state. The coating layer is preferably in a substantially non-foamed state. "Substantially non-foamed" means that almost no bubble structure is formed.
[0051] Next, the coating layer constituting the multi-layered expanded beads will be described. Examples of the resin constituting the coating layer include polyolefin resins. Examples of the polyolefin resin include polyethylene resins such as linear low-density polyethylene, low-density polyethylene, and high-density polyethylene, polypropylene resins such as propylene-ethylene copolymers, propylene-butene copolymers, and propylene-ethylene-butene copolymers, and mixtures thereof. From the viewpoint of excellent adhesion to the foam layer, the polyolefin resin of the coating layer is preferably a polypropylene resin and / or a polyethylene resin, and more preferably a polypropylene resin. It is more preferable that the base resin constituting the coating layer is at least one selected from a propylene-ethylene copolymer, a propylene-butene copolymer, and a propylene-ethylene-butene copolymer. In addition, the coating layer made of a polypropylene resin and / or a polyethylene resin has improved adhesion between the foam layer and the coating layer, and can stably obtain a molded body having good mechanical properties. The base resin composed of at least one selected from the group consisting of propylene-ethylene copolymer, propylene-butene copolymer, and propylene-ethylene-butene copolymer may be composed of a single copolymer or a mixture of multiple copolymers. Furthermore, from the viewpoint of the fusion property, adhesiveness, etc., it is preferable that the base resin is obtained by using a metallocene polymerization catalyst.
[0052] When the resin constituting the coating layer is a polyolefin-based resin, the melting point Tms of the polyolefin-based resin is preferably lower than the melting point Tmc of the polypropylene-based resin constituting the foam layer, for example. That is, it is preferable that Tms < Tmc. In this case, the fusion property between the foam particles during molding is improved, and a molded body excellent in fusion property can be produced at a low temperature (specifically, low steam pressure) during in-mold molding. From the viewpoint of further improving this effect, it is preferable that Tmc - Tms ≧ 1 (°C), more preferably Tmc - Tms ≧ 3 (°C), and even more preferably Tmc - Tms ≧ 5 (°C). From the viewpoint of further suppressing the peeling between the foam layer and the coating layer and the adhesion of the resin to the mold during in-mold molding, it is preferable that Tmc - Tms ≦ 30 (°C), more preferably Tmc - Tms ≦ 25 (°C), and even more preferably Tmc - Tms ≦ 20 (°C).
[0053] From the viewpoint of easily suppressing the adhesion of the resin to the mold, the melting point Tms of the polyolefin-based resin constituting the coating layer is preferably 100°C or higher, more preferably 110°C or higher, and even more preferably 120°C or higher. On the other hand, from the viewpoint of easily enhancing the fusion property of the foam particles during molding, the melting point Tms of the polyolefin-based resin constituting the coating layer is preferably 150°C or lower, more preferably 145°C or lower, and even more preferably 140°C or lower. The melting point of the polyolefin-based resin constituting the coating layer is determined based on JIS K7121:1987. Specifically, it is determined under the same conditions and by the same method as those for the polypropylene-based resin constituting the above-mentioned single-layer foam particles.
[0054] When the expanded beads of the present invention are multi-layered expanded beads, the ratio of the coating layer in the expanded beads is preferably 0.5% by mass or more and 10% by mass or less. In this case, it is possible to stably obtain an expanded bead molding having excellent mechanical properties while improving the moldability of the expanded beads in the mold. From the viewpoint of improving the effect of excellent balance between the moldability in the mold and the mechanical properties, the ratio of the coating layer in the multi-layered expanded beads is more preferably 1% by mass or more and 8% by mass or less, and even more preferably 2% by mass or more and 6% by mass or less.
[0055] Next, an example of the method for producing the expanded beads of the present invention will be described. The expanded beads can be produced, for example, by a so-called dispersion medium release foaming method, in which resin particles or multi-layered resin particles are produced (resin particle production step), the resulting resin particles are dispersed in a dispersion medium (e.g., water) (dispersion step), the resin particles are impregnated with a foaming agent (foaming agent impregnation step), and the expandable resin particles containing the foaming agent are released together with the dispersion medium under low pressure (foaming step), to produce the expanded beads.
[0056] (Resin particle manufacturing process) The resin particles are produced, for example, as follows. First, a polyolefin resin and additives such as a bubble nucleating agent, which are added as necessary, are fed into an extruder, and heated and kneaded to form a resin melt kneaded product. The resin melt kneaded product is then extruded as a tubular strand having a through hole from a small hole of a die attached to the tip of the extruder, and cooled and cut to obtain resin particles. The tubular strand having a through hole is formed by passing the molten resin kneaded product through a die having a flow path formed by a metal fitting provided in the flow path of the die attached to the tip of the extruder, the flow path having a cross-sectional shape corresponding to the cross-sectional shape of the resin particles having a through hole. The extrudate is cut by, for example, a pelletizer. The cutting method can be selected from a strand cut method, a hot cut method, an underwater cut method, and the like. In this way, a cylindrical single-layer resin particle having a through hole can be obtained. When forming a multilayer resin particle, a foam layer forming extruder and a coating layer forming extruder are used to obtain a resin melt kneaded product of each raw material, and each melt kneaded product is introduced into a die and merged in the die to form a sheath-core type composite melt resin kneaded product consisting of a non-foamed cylindrical foam layer forming molten resin kneaded product and a non-foamed coating layer forming molten resin kneaded product that covers the outer peripheral surface part of the foam layer forming molten resin kneaded product, and the composite melt resin kneaded product is extruded into a strand shape having a through hole from a fine hole in a die attached to the tip of the extruder, while being cooled and cut, thereby obtaining a multilayer resin particle.
[0057] When magnesium silicate is contained in the expanded beads, it is preferred to add magnesium silicate to the resin for forming the expanded layer of the single-layer resin beads or to the resin for forming the coating layer of the multi-layer expanded beads in the production process of these resin beads.
[0058] The particle diameter of the resin particles is preferably 0.1 mm to 3.0 mm, more preferably 0.3 mm to 1.5 mm. The length / outer diameter ratio of the resin particles is preferably 0.5 to 5.0, more preferably 1.0 to 3.0. The average mass per particle (obtained from the mass of 200 randomly selected particles) is preferably 0.1 mg to 20 mg, more preferably 0.2 mg to 10 mg, even more preferably 0.3 mg to 5 mg, and particularly preferably 0.4 mg to 2 mg. The mass ratio of the foamed layer and the coating layer in the multi-layered resin particles (specifically, the mass of the foamed layer: the mass of the coating layer) is preferably 99.5:0.5 to 90:10, more preferably 99:1 to 92:8, and even more preferably 98:2 to 94:6. The mass ratio is expressed as the mass of the foamed layer: the mass of the coating layer.
[0059] Additives such as bubble adjusters, crystal nucleating agents, colorants, flame retardants, flame retardant assistants, plasticizers, antistatic agents, antioxidants, UV inhibitors, light stabilizers, conductive fillers, and antibacterial agents can be added to the resin particles as needed. Examples of bubble adjusters include inorganic powders such as mica, zinc borate, calcium carbonate, silica, titanium oxide, gypsum, zeolite, borax, aluminum hydroxide, and carbon; and organic powders such as phosphoric acid-based nucleating agents, phenol-based nucleating agents, amine-based nucleating agents, and polyethylene fluoride-based resin powder. When a bubble adjuster is added, the content of the bubble adjuster is preferably 0.01 parts by mass or more and 1 part by mass or less relative to 100 parts by mass of the polypropylene-based resin.
[0060] (Dispersion process) The dispersion step is a step of dispersing resin particles in an aqueous medium. As the resin particles, the above-mentioned single-layer resin particles or the above-mentioned multi-layer resin particles are used.
[0061] An aqueous medium is used as a dispersion medium (specifically, a liquid) for dispersing the single-layer resin particles or the multi-layer resin particles in a closed container. The aqueous medium is a dispersion medium (specifically, a liquid) whose main component is water. The proportion of water in the aqueous medium is preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more. Examples of dispersion media other than water in the aqueous medium include ethylene glycol, glycerin, methanol, and ethanol. As the aqueous medium, water is particularly preferred.
[0062] When magnesium silicate is to be attached to the expanded beads, it is preferable to add 0.1 to 15 parts by mass of magnesium silicate per 100 parts by mass of resin particles and disperse it in an aqueous medium. The magnesium silicate dispersed in an aqueous medium acts as an inorganic dispersant and is attached to the resin particles in the dispersion step, and when the resin particles are expanded in the expansion step described later, the magnesium silicate remains on the surface of the expanded beads, so that expanded beads having magnesium silicate attached uniformly to the surface of the expanded beads can be obtained. Note that when the resin particles contain magnesium silicate and it is not necessary to attach magnesium silicate to the expanded beads, it is not necessarily necessary to use magnesium silicate as an inorganic dispersant.
[0063] In the dispersion step, in order to prevent the resin particles heated in the container from fusing together, other inorganic dispersants may be added to the aqueous medium in addition to magnesium silicate as described above within a range that does not impair the intended effects of the present invention. Examples of other inorganic dispersants include inorganic fine particles such as aluminum oxide, tricalcium phosphate, magnesium pyrophosphate, and zinc oxide. These inorganic fine particles may be used alone or in combination of two or more kinds. The dispersant is preferably added in an amount of from 0.001 to 5 parts by mass per 100 parts by mass of the resin particles.
[0064] In addition, additives other than the inorganic dispersant include a dispersion aid, a surfactant, and the like. Examples of the dispersion aid include aluminum sulfate. Examples of the surfactant include anionic surfactants such as sodium alkylbenzenesulfonate, sodium dodecylbenzenesulfonate, and sodium alkanesulfonate. The surfactants may be used alone or in combination of two or more. The amount of the dispersion aid added is preferably 0.001 to 1 part by mass per 100 parts by mass of the resin particles.
[0065] (Foaming agent impregnation process) The foaming agent impregnation step is a step of impregnating the resin particles with a foaming agent. The foaming agent impregnation step may be performed after the dispersion step, or the foaming agent impregnation step may be performed partly or entirely overlapping with the dispersion step.
[0066] In the foaming agent impregnation step, for example, a container containing resin particles is sealed, and a foaming agent is added to the sealed container to impregnate the resin particles with the foaming agent. This allows the production of expandable resin particles containing a foaming agent. For example, a physical foaming agent is used as the foaming agent. The addition of the physical foaming agent to the sealed container may be performed at any timing before the resin particles are expanded. A solid foaming agent may be added to the aqueous medium together with the resin particles during the dispersion step, and the foaming agent that has become gaseous by heating or the like may then be impregnated into the resin particles. In addition, in parallel with the dispersion step or after the completion of the dispersion step, a gaseous foaming agent may be pressed into the sealed container to impregnate the resin particles with the foaming agent. For example, when carbon dioxide is used as a physical foaming agent, a solid foaming agent (e.g., dry ice) may be added to the aqueous medium together with the resin particles during the dispersion step, or gaseous carbon dioxide may be pressed into the sealed container during or after the dispersion step. When the resin particles are impregnated with the foaming agent, the impregnation of the resin particles with the foaming agent can be promoted by heating and / or pressurizing the inside of the sealed container.
[0067] The temperature of the aqueous medium is increased at a rate of 1° C. / min to 5° C. / min, and a holding step is provided during the temperature increase.
[0068] (holding process) In the holding step, the expanded beads are held at a predetermined temperature to adjust the crystalline state. The holding step is carried out by adjusting the heating rate of the sealed container or by adjusting the holding temperature and holding time of the sealed container in the dispersion step and / or the foaming agent impregnation step. The crystalline state is adjusted, for example, so that an endothermic peak (i.e., a high-temperature peak) appears on the high-temperature side of the endothermic peak (i.e., a resin-specific peak) of the main component of the base resin constituting the foam layer of the expanded beads in a DSC curve obtained by heat flux differential scanning calorimetry. By adjusting the high-temperature peak, the molding condition range (specifically, molding temperature, molding pressure) under which a good molded body can be obtained can be widened, and the compression strength of the obtained molded body can be improved.
[0069] In general, the high-temperature peak is adjusted as follows. In the holding step, the temperature increase is stopped at an arbitrary temperature Ta within a range of at least 15°C lower than the resin melting point Tm of the resin particles and lower than the melting end temperature Te of the resin particles, and the resin particles in which secondary crystals have been formed are expanded by holding the temperature Ta for a sufficient time, preferably about 10 to 60 minutes, thereby adjusting the high-temperature peak. The high-temperature peak can also be adjusted in the foaming step described below. In this case, the temperature Tb is adjusted to an arbitrary temperature within the range of (Tm-5°C) to (Te+5°C), and the resin particles are released from the container to a low-pressure region at that temperature and expanded to obtain expanded beads. The calorific value of the high-temperature peak of the expanded beads tends to increase as the temperature Ta or Tb is lower within the above temperature range and the holding time is longer. Usually, the heating rate in the foaming step is 0.5 to 5°C / min. By repeating preliminary experiments taking these points into consideration, the manufacturing conditions for expanded beads that show the desired high-temperature peak calorific value can be easily and accurately known.
[0070] (foaming agent) The blowing agent is appropriately selected from among the general blowing agents used to obtain expanded particles. As the blowing agent, a physical blowing agent is preferable. As the physical blowing agent, an inorganic physical blowing agent and / or an organic physical blowing agent can be used. As the inorganic physical blowing agent, carbon dioxide, air, nitrogen, helium, argon, water, etc. can be mentioned. As the organic physical blowing agent, aliphatic hydrocarbons such as propane, butane, hexane, etc.; alicyclic hydrocarbons such as cyclopentane, cyclohexane, etc.; halogenated hydrocarbons such as 2,3,3,3-tetrafluoropropene, trans-1,3,3,3-tetrafluoropropene, trans-1-chloro-3,3,3-trifluoropropene, etc. can be mentioned.
[0071] These physical foaming agents may be used alone or in combination of two or more. Of these foaming agents, preferably, foaming agents mainly composed of inorganic physical foaming agents such as carbon dioxide, nitrogen, and air are used, and more preferably, carbon dioxide is used. In this specification, "mainly composed of inorganic physical foaming agent" means that the physical foaming agent contains 50 mol% or more of inorganic physical foaming agent. It is preferable that the physical foaming agent contains 70 mol% or more of inorganic physical foaming agent, more preferably 90 mol% or more, and it is even more preferable that the physical foaming agent consists of only inorganic physical foaming agent.
[0072] The amount of the physical foaming agent is appropriately determined according to the type of base resin constituting the resin particles, the type of foaming agent, the bulk density of the target expanded particles, etc. In particular, it is preferable to determine the amount of the physical foaming agent according to the desired bulk density. For example, when carbon dioxide is used as the physical foaming agent, the amount of carbon dioxide is preferably 0.1 parts by mass or more and 30 parts by mass or less, more preferably 0.5 parts by mass or more and 15 parts by mass or less, and even more preferably 1 part by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the multilayer resin particles.
[0073] (Foaming process) In the expansion step, resin particles containing a blowing agent (i.e., expandable resin particles) are released from a container together with an aqueous medium and expanded to produce expanded particles. Specifically, the expandable resin particles are expanded by releasing the expandable resin particles together with an aqueous medium under a pressure lower than the internal pressure of the sealed container. According to this expansion method, expanded particles having a low bulk density can be easily obtained.
[0074] The pressure inside the sealed container during expansion is preferably 0.5 MPa (G: gauge pressure) or more. On the other hand, the pressure inside the sealed container is preferably 4.0 MPa (G) or less, and more preferably 3.0 MPa (G) or less. If it is within this range, the expanded beads can be safely produced without risk of damage or explosion of the sealed container.
[0075] The bulk density of the expanded beads can be adjusted, for example, by appropriately changing the expansion conditions, such as the temperature and pressure in the sealed container when the content of the sealed container is released in the expansion step. Furthermore, in the case of producing expanded beads having a lower bulk density, a multi-stage expansion process such as a two-stage expansion process can be carried out. In the two-stage expansion process, first, the expanded beads obtained by the above-mentioned dispersion medium release foaming method are stored in a pressurizable sealed container, and a gas such as air is forced into the sealed container to perform a pressurization treatment to increase the pressure in the bubbles of the expanded beads (i.e., the internal pressure). Thereafter, the expanded beads with the increased internal pressure are taken out of the sealed container, and are expanded by heating them using steam or hot air. By carrying out the two-stage expansion process, expanded beads having a lower bulk density (two-stage expanded beads) can be obtained. In addition, compared to a method of obtaining expanded beads having a low bulk density by a single expansion process, the method of obtaining expanded beads having a low bulk density by carrying out the two-stage expansion process makes it easier to increase the bubble diameter of the expanded beads finally obtained. The expanded bead molding produced using the expanded beads obtained by carrying out the two-stage expansion process can further suppress the occurrence of uneven color tone. Therefore, in the case of producing expanded beads containing a colorant, it is preferable to carry out the two-stage expansion process. In the present invention, if the first-stage expanded beads satisfy the configuration of the present invention, the variation in the expansion ratio of the second-stage expanded beads will also be small. Furthermore, when the second-stage expanded beads are used to obtain an expanded bead molding, the variation in the expansion ratio of the expanded bead molding will also be small.
[0076] In the resin particle production process, the average diameter d of the through holes of the resulting expanded beads can be adjusted by adjusting the diameter dr of the through holes of the resin particles. The diameter dr of the through holes can be adjusted, for example, by changing the diameter of the small holes at the die outlet for forming the through holes. In addition, the average outer diameter and average wall thickness of the expanded beads can be adjusted to the desired range by adjusting the particle diameter and average mass of the resin particles.
[0077] The average pore size dr of the through holes of the resin particles is preferably less than 0.8 mm, more preferably less than 0.2 mm. If the average pore size dr is less than 0.2 mm, the average pore size d of the through holes is 1 mm or less, and the ratio d / D of the average pore size d to the average outer diameter D is 0.4 or less can be more reliably produced. The average pore size dr of the through holes of the resin particles is preferably 0.1 mm or more. If the average pore size dr is within this range, the production stability of the resin particles having through holes is ensured.
[0078] For the same reasons as those for the expanded particles, the ratio dr / Dr of the average pore size dr to the average outer diameter Dr of the resin particles is preferably 0.4 or less, more preferably 0.3 or less, even more preferably 0.25 or less, and particularly preferably 0.2 or less. The ratio dr / Dr of the average pore size dr to the average outer diameter Dr of the resin particles is preferably 0.1 or more.
[0079] The average pore diameter dr of the through holes of the resin particles is determined as follows. The resin particles are cut perpendicularly to the penetration direction of the through holes at the position where the area of the cut surface is approximately maximum. The cut surface of each resin particle is photographed, the cross-sectional area of the through hole portion (specifically, the opening area) is determined, and the diameter of a virtual perfect circle having the same area as that area is calculated and used as the pore diameter of the through holes of one resin particle. This operation is performed on 50 or more expanded beads randomly selected from the expanded particle group, and the arithmetic mean value of the obtained measured values is used as the average pore diameter dr. In addition, when the size of the through hole of each resin particle is not uniform in the through hole diameter in the through hole direction, the through hole diameter of each resin particle is determined by measurement at the position where the area of the cross section of the resin particle is approximately maximum, as described above.
[0080] The average outer diameter Dr of the resin particles is determined as follows. A resin particle is cut perpendicularly to the penetrating direction of the through holes at a position where the area of the cut surface is approximately maximum. A photograph of the cut surface of each resin particle is taken to determine the cross-sectional area of the resin particle (specifically, the cross-sectional area including the opening of the through hole), and the diameter of a virtual perfect circle having the same area as that area is calculated and used as the outer diameter of one resin particle. This operation is performed on 50 or more expanded particles randomly selected from the expanded particle group, and the arithmetic mean value of the obtained measured values is used as the average outer diameter Dr. In addition, when the outer diameter of each resin particle is not uniform in the penetration direction, the outer diameter of each resin particle is determined by measurement at the position where the area of the cross section of the resin particle in the direction perpendicular to the penetration direction is approximately maximum, as described above.
[0081] In the strand cut method, the particle diameter, length / outer diameter ratio and average mass of the resin particles can be adjusted by appropriately changing the extrusion speed, take-up speed, cutter speed, etc. when extruding the molten resin mixture.
[0082] Next, the expanded polyolefin resin bead molding of the present invention will be described. The polyolefin resin foamed bead molding of the present invention (hereinafter, also simply referred to as foamed bead molding or molding) is obtained by in-mold molding using the polyolefin resin foamed beads, and is composed of a large number of foamed beads fused to each other.
[0083] Specifically, the in-mold molding is carried out as follows. First, the foamed beads are filled into a mold having a cavity corresponding to the shape of the desired molded article. Next, a heating medium such as steam is introduced into the mold to heat the foamed beads filled in the mold. The foamed beads in the cavity are further expanded by heating and are fused to each other. As a result, the foamed beads are integrated with each other, and a molded article corresponding to the shape of the cavity is obtained.
[0084] The density of the foamed bead molding is 10 kg / m 3 More than 100kg / m 3If the density of the molded body is within this range, the light weight and rigidity of the molded body can be improved in a well-balanced manner. In order to further improve the rigidity of the molded body, the density of the molded body is preferably 20 kg / m or less. 3 In order to make the compact lighter, the compact density of the compact is preferably 80 kg / m or more. 3 More preferably, it is 50 kg / m or less. 3 It is even more preferable that:
[0085] The density of a green body is calculated by multiplying the weight (g) of the green body by the volume (cm) calculated from the external dimensions of the green body. 3 In addition, when it is not easy to determine the volume from the outer dimensions of the molded body, for example, because the molded body has a complex shape as a whole or a complex shape partially, the volume of the molded body can be determined by the submersion method.
[0086] The expanded bead molding of the present invention has magnesium silicate present on the surface portion as described above, and therefore has a small variation in apparent density.
[0087] The expanded bead molding of the present invention is produced by molding expanded beads having through holes in a mold, and can be used for various applications such as packaging materials, automotive parts, and cushioning materials. EXAMPLES
[0088] The present invention will now be described in more detail with reference to examples, although the present invention is not limited to these examples.
[0089] In the examples and comparative examples, the following raw materials were used.
[0090] (Polypropylene resin) (1) Abbreviation "Resin 1": Ethylene-propylene random copolymer (ethylene content 3.1% by mass, melting point 151°C, melt flow rate 5g / 10min. (230°C, load 2.16kg)) (2) Abbreviation "Resin 2": Ethylene-propylene, butene-random copolymer (ethylene content 3.8% by mass, butene content 3.8% by mass, melting point 135°C, melt flow rate 5g / 10min. (230°C, load 2.16kg)) (3) Abbreviation "Resin 3": Ethylene-propylene random copolymer (ethylene content 4.5 mass%, melting point 133°C, melt flow rate 24g / 10min. (230°C, load 2.16kg))
[0091] (Dispersant: inorganic compound) (1) Abbreviation "Dispersant 1": Magnesium silicate; "Fine Talc SG-90" manufactured by Nippon Talc Co., Ltd. (average particle size 3.0 μm, silicon dioxide content 62% by mass) (2) Abbreviated name "Dispersant 2"; Kaolin; "Kaolin ASP-200" manufactured by BASF Japan (average particle size 2.6 μm)
[0092] (Multi-layer resin particle manufacturing equipment) A manufacturing device was used in which a cylindrical twin-screw extruder for forming a foam layer with an inner diameter of 50 mm and a single-screw extruder for forming a coating layer with an inner diameter of 30 mm were connected to a die for forming a multilayer strand, and the resin molten mixture for forming the foam layer and the resin molten mixture for forming the coating layer were laminated in the die and co-extruded. A metal fitting was attached to the tip of the outlet of the flow path of the die so that a through hole could be formed in the strand extruded through the die for forming the multilayer strand, and a cross-sectional shape having a through hole was formed.
[0093] Examples 1 to 5, Comparative Example 1, Reference Example 1 The polypropylene resin of the type shown in Table 1, 0.05 mass% zinc borate (cell regulator), and 2.6 mass% furnace black were fed into a twin-screw extruder for forming a foam layer, and melt-kneaded to produce a resin melt-kneaded product for forming a foam layer.
[0094] A polypropylene resin of the type shown in Table 1 and 2.6 mass % of furnace black were supplied to the extruder for forming the covering layer, and melt-kneaded to prepare a resin melt-kneaded product for forming the covering layer.
[0095] The resin melt kneaded products for forming each layer were adjusted in discharge rate from each extruder so that the foam layer:coating layer ratio was 95:5, and the mixtures were introduced into a multilayer strand forming die and merged in the die, and a multilayer strand having a two-layer structure (a sheath-core structure of a cylindrical foam layer and a coating layer) was extruded from the die hole provided downstream of the die. The extruded strand was cooled with water and cut with a pelletizer to obtain multilayer resin particles with an average mass of 1.5 mg per piece.
[0096] (Production of multi-layer foamed beads) The multilayer resin particles in the amounts shown in Table 1 and water in the amount shown in Table 1 were supplied into a sealed container having a capacity of 400 L. In addition, an inorganic dispersant of the type and amount shown in Table 1 and a surfactant (product name: NEOGEN S-20F, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., aqueous solution of sodium dodecylbenzenesulfonate) in the amount shown in Table 1 were added to the sealed container in an amount per 100 parts by mass of the multilayer resin particles.
[0097] Next, carbon dioxide was injected as a blowing agent into the sealed container at room temperature, and the pressure was increased to 1.0 MPa (G) in gauge pressure. In this specification, the pressure with (G) means a gauge pressure, i.e., a pressure value based on atmospheric pressure. Thereafter, the sealed container was heated at a temperature increase rate of 2°C / min while stirring until the foaming temperature shown in Table 1 was reached, carbon dioxide was injected, and the pressure was increased until the gauge pressure reached the equilibrium vapor pressure shown in Table 1, and the same temperature was maintained for 6 minutes, and the resulting expanded particles were adjusted to have a high-temperature peak in the endothermic curve measured by DSC.
[0098] Thereafter, the contents (expandable resin particles and water) of the sealed container were released under atmospheric pressure to obtain first-stage expanded particles (specifically, first-stage expanded particles).
[0099] [Table 1]
[0100] The first-stage expanded particles obtained as described above were left to stand for 24 hours in an environment of 23°C temperature, 50% relative humidity, and 1 atm to cure. The cured first-stage expanded particles were then loaded into a pressurizable sealed container, and the pressure in the sealed container was increased from normal pressure to pressurize the first-stage expanded particles. The pressurized state of the first-stage expanded particles was maintained, the pressure in the bubbles of the first-stage expanded particles was increased, and the expanded particles were removed from the sealed container to obtain expanded particles for second-stage expansion production in which the internal pressure of the bubbles of the expanded particles was pressurized. The internal pressure of the expanded particles is shown in the column of second-stage expanded particle production conditions in Table 2.
[0101] The first-stage expanded beads were then fed into a second-stage expansion device. Steam was fed into the device to expand the beads for second-stage expansion. The resulting expanded beads were dried at 23°C for 12 hours to obtain second-stage expanded beads. The second-stage expanded beads obtained by the second-stage expansion were used to measure various physical properties and were further used for the production of expanded bead moldings. The physical properties of the resulting second-stage expanded beads are shown in Table 2.
[0102] (Production of foamed bead moldings) The second-stage foamed particles were filled in a pressurizable sealed container, and the pressure in the sealed container was increased from normal pressure to pressurize the second-stage foamed particles. The pressurized state of the foamed particles was maintained for 24 hours to increase the pressure in the bubbles of the second-stage foamed particles. Thereafter, the first-stage foamed particles were taken out of the sealed container to obtain foamed particles with an internal pressure of the bubbles of the foamed particles of 0.1 MPa (G). These second-stage foamed particles were filled into a molding die having a molding cavity capable of molding a plate-shaped molded body of length 300 mm x width 250 mm x height 60 mm, and molding was performed by the following heating method. Steam was supplied to the die with the drain valves provided on both sides of the die open to perform preheating (exhaust process). Thereafter, steam was supplied from one side of the die to heat it, and further steam was supplied from the other side of the die to heat it. Subsequently, steam was supplied from both sides of the die to heat it. After heating, the pressure was released and the molded product was cooled with water until the surface pressure due to the foaming force of the molded product reached 0.04 MPa (G), after which the mold was opened and the molded product was taken out. This molded product was cured in an oven at 80°C for 12 hours, and then slowly cooled to room temperature to obtain a plate-shaped molded product. The physical properties of the obtained molded product are shown in Table 2.
[0103] [Table 2]
[0104] Examples 1 to 5 are examples in which expanded beads were produced under the same conditions, except that the amount of magnesium silicate used as a dispersant was changed. Comparing Examples 1 to 5, it was shown that the water content was reduced as the amount of magnesium silicate was increased, and the expansion ratio of the expanded beads was reduced, which resulted in reduced variation in the density of the resulting molded body.
[0105] Reference Example 1 is an example in which expanded beads were produced in the same manner as in Example 3, except that kaolin was used as a dispersant and no through holes were formed. Since there were no through holes, it was found that there was no variation in the density of the molded body even though magnesium silicate was not present. Comparative Example 1 is an example in which expanded beads were produced in the same manner as in Example 3, except that kaolin was used as a dispersant. The moisture content of the obtained first-stage expanded beads was high, and the density of the obtained molded bodies varied greatly.
[0106] The bulk density, high temperature peak calorific value, moisture content, and residual magnesium silicate ratio of the first-stage expanded beads in Table 1 were measured by the above-mentioned methods.
[0107] The bulk density, average outer diameter D, average pore diameter d, and average wall thickness t of the second-stage expanded beads in Table 1 were measured by the above-mentioned methods.
[0108] The average cell diameter of the expanded beads in Table 1 was measured as follows. (average bubble diameter) The expanded beads were roughly divided into two parts passing through the center of the expanded beads, and a photograph of the cut surface was taken using a scanning electron microscope. In the obtained cross-sectional photograph, four lines were drawn at equal angles from the outermost surface of the expanded beads through the center to the outermost surface on the opposite side. The number of bubbles intersecting each line was counted, and the total length of the four lines was divided by the total number of bubbles intersecting the lines to obtain the average bubble diameter of one expanded bead. This operation was performed on 10 randomly selected expanded beads, and the arithmetic mean of the values obtained for each expanded bead was used as the average bubble diameter of the two-stage expanded beads in this specification.
[0109] The lower limit molding pressure and moldable pressure range in Table 1 were determined as follows, and the water cooling time was evaluated as follows. The fusion property and moldability (density variation of molded body) were evaluated as follows.
[0110] (Molding pressure range) Using the above molding method, molding was performed at each molding pressure, increasing the molding pressure (molding heating steam pressure) by 0.02 MPa in a wide molding pressure range. The obtained molded bodies were evaluated from the viewpoints of secondary foaming, fusion, and recovery, and the molding pressure at which a molded body that passed all the requirements was determined as the moldable pressure. This moldable pressure was evaluated as 2 points or more as ◎, 1 point as ◯, and no range as ×, and is listed in the column of moldable pressure range in Table 1.
[0111] (Lower limit molding pressure) Within the above-mentioned moldable pressure range, the lowest molding pressure is shown in Table 1 as the lower limit molding pressure.
[0112] (Water cooling time evaluation) The water cooling time at the above-mentioned lower limit molding pressure was evaluated according to the following criteria: A water cooling time of 80 seconds or less was evaluated as ⊚, 80 to 100 seconds was evaluated as ◯, and 100 seconds or more was evaluated as x. The results are shown in Table 1.
[0113] (Fusing ability) The obtained molded article was cut with a sharp blade along the edge to approximately the center of the molded article, and the cut portion was then broken by hand, and the number of all the expanded particles and the broken expanded particles present on the broken surface were counted, and the ratio of the broken expanded particles to the total expanded particles was calculated (%). The ratio of broken expanded particles was evaluated as 90% or more as ◎, 90-70% as ○, and 70% or less as ×, and the results are shown in Table 1.
[0114] (Moldability (density variation of green body)) The molding was repeated 10 times at the lower limit molding pressure using the above molding method, and the density of the resulting 10 molded bodies was measured. The density distribution of the resulting molded bodies was evaluated as follows: those with a density distribution of ±5% or less of the average value were rated as ⊚, those with a density distribution of ±10% or less were rated as ◯, and those with a density distribution of more than ±10% were rated as ×. The results are shown in Table 1.
[0115] (Ratio of magnesium silicate present on the surface) The proportion of magnesium silicate present on the surface of the expanded beads was measured by the following method. First, the multilayer resin particles used in the production of the multilayer expanded beads and the resulting multilayer expanded beads were prepared. In the process of obtaining multilayer expanded beads from the multilayer resin particles, the composition of the particles themselves did not change. In addition, magnesium silicate was attached to the surface of the multilayer expanded beads by the dispersion process. Therefore, the ash content (A1: wt%) of the multilayer expanded beads and the ash content (A2: wt%) of the multilayer resin particles before being dispersed in an aqueous medium were measured, and the amount of magnesium silicate attached on the surface of the expanded beads was calculated by subtracting the ash content (A2: wt%) of the multilayer resin particles from the ash content (A1: wt%) of the multilayer expanded beads, which was used as the proportion of magnesium silicate present on the surface of the expanded beads.
[0116] The ash content was measured based on JIS K 6226-2. The measuring device used was a thermogravimetric analyzer TGA701 manufactured by LECO. Approximately 5 g of foamed particles were collected as a measurement sample and placed in a crucible, and the inside of the heating furnace was made into a nitrogen gas flow. (1) In a nitrogen atmosphere, the temperature of the heating furnace was heated from room temperature to 105°C at a heating rate of 10°C / min, then (2) it was held at 105°C until the measured weight was equilibrated, (3) it was heated from 105°C to 450°C at a heating rate of 10°C / min, (4) it was held at 450°C until the measured weight was equilibrated, (5) the heating furnace gas flow was changed from nitrogen to air, and it was heated from 450°C to 950°C at a heating rate of 10°C / min, (6) the weight W1 of the combustion residue after holding at 950°C for 10 minutes was obtained, and (7) it was cooled to room temperature. The weight W1 of the combustion residue was divided by the weight of the measurement sample placed in the crucible, and the resulting value was multiplied by 100 to obtain the ash content A1 (wt%) in the expanded beads. The ash content A2 (wt%) in the resin beads was also measured in the same manner, and the proportion As of magnesium silicate present in the surface portion of the expanded beads was calculated from the following formula (2). A2-A1 = As (wt%) (2)
[0117] The moisture content of the expanded beads was measured by the following method. The expanded beads produced by the expansion process or the two-stage expansion process and immediately after curing were completed were weighed and used as a measurement sample. Next, the measurement sample was heated to a temperature of 100°C using a halogen moisture meter (HX204) manufactured by METTLER TOLEDO, and maintained at 100°C for 60 seconds until no weight change occurred, and then further heated to 160°C and maintained at 160°C for 90 seconds until no weight change occurred, thereby vaporizing the moisture inside the measurement sample. The weight loss due to heating at this time was divided by the weight of the expanded beads before heating and converted into a percentage to calculate the moisture content (%).
[0118] The bulk density of the expanded particles was measured by the following method. First, the expanded particles to be measured were left in an environment of 23°C temperature, 50% relative humidity, and 1 atm for 24 hours or more. Then, a mass W (unit: g) of expanded particles was filled into a measuring cylinder, and the bottom of the measuring cylinder was lightly tapped on the floor several times to stabilize the filling height of the expanded particles in the measuring cylinder. The bulk volume V (unit: L) of the expanded particles indicated by the graduations on the measuring cylinder was read, and the mass W of the expanded particles was divided by the bulk volume V of the expanded particles (i.e., W / V). The value obtained in this way was expressed in kg / m 3 The same measurement was repeated 10 times for different samples, and the average was calculated to obtain the bulk density (unit: kg / m 3 ) was obtained. In addition, the variation of the expansion ratio was evaluated as follows: those with a variation of ±5% or less from the average of the 10 measured values were evaluated as ◎, those with a variation of ±10% or less were evaluated as ◯, and those with a variation of more than ±10% were evaluated as ×. These are shown in Table 1 as the expansion ratio variation.
Claims
1. The expanded polyolefin resin beads are characterized in that they are polyolefin resin expanded beads having through holes, magnesium silicate is present on the surface portion of the expanded beads, and the proportion of magnesium silicate present on the surface portion of the expanded beads is 0.1 mass% or more.
2. 2. The expanded polyolefin resin beads according to claim 1, wherein the through holes of the expanded polyolefin resin beads have an average pore diameter d of 0.1 mm or more and 5 mm or less.
3. The polyolefin resin expanded beads according to claim 2, wherein the average pore diameter d of the through holes of the polyolefin resin expanded beads is 0.1 mm or more and less than 1 mm, and the ratio d / D of the average pore diameter d to the average outer diameter D of the polyolefin resin expanded beads is 0.4 or less.
4. 4. The expanded polyolefin resin beads according to claim 3, wherein the expanded polyolefin resin beads have an average outer diameter D of 2 mm or more and 5 mm or less, and an average wall thickness t of 1.2 mm or more and 2 mm or less.
5. The polyolefin-based resin expanded particles according to any one of claims 1 to 4, which have a polyolefin-based resin foamed layer and a polyolefin-based resin coating layer, and the coating layer covers all or a part of the foamed layer.
6. 5. A polyolefin resin foamed bead molding obtained by molding the foamed bead according to claim 1 in a mold.
Citation Information
Patent Citations
Polypropylene-based resin foam particle, and foam particle molding
JP2022096231A